Modelling and Simulation of a Network Management System using Hierarchical Coloured Petri Nets: Extended version - Christensen, Søren; Jepsen, Leif Obel (DAIMI Report Series, 1994)
Development of distributed software systems is a complex task. This paper argues that design and specification can be supported by modelling and simulation using Hierarchical Coloured Petri Nets (CP-nets). This conclusion is based on a case study of a project in which CP-nets were used in the detailed design of a software module. The software module is part of the Network Management System of the RcPAX X.25 wide area network. The module was designed using the Design/CPN tool which allows editing and simulation of CP-nets. Furthermore invariant techniques were used to prove properties of the module. Genoptrykt i Oktober 1994 i 100 eksemplarer.